Effect of Dope Composition and Additive Agent on the Properties of La0.6Sr04Co0.2Fe0.8O3-? Asymmetric Flat Membranes - Nurherdiana, Silvana Dwi; Habib, Mohammad Hasnan; Utomo, Wahyu Prasetyo; Kusumawati, Yuly; Akhlus, Syafsir; Fansuri, , Hamzah (Nusantara Science and Technology Proceedings)
In this study, the La0.6Sr0.4Co0.2Fe0.8O3-? (LSCF 6428) asymmetric flat membrane was successfully fabricated using a based-phase inversion technique. The effect of different dope composition and molecular weight of polyethylene glycol (PEG) as a pore-forming agent were investigated to identify the membrane properties in term of uniformly pore configuration and the mechanical strength. The result showed that the addition of dimethyl sulfoxide (DMSO) as the solvent in varied compositions exhibits different morphology and the most uniform finger-like pores with a diameter of 22 ?m were formed using 5.0 ml DMSO. Based on the uniformity of the pores, 5.0 ml DMSO was further used to study the effect of PEG addition. A highly uniform porous configuration with a pore diameter of 17 ?m, less dense layer thickness, the high mechanical strength of 507.2 Hv, and good thermal expansion behavior was achieved when 0.39% PEG 8000 was added. Such PEG 8000 is promoted additive to adjust the LSCF membrane porous configuration parameter to improve oxygen permeation and catalytic performance on partial oxidation of methane.